Marriage Customs of Chinese Uyghurs and Javanese People - Rasyid, Hemas Mutia; Lestari, Fitri Khairunisa; Fatiha, Anisa Aulia (Journal of Maobi, 2024)
Marriage is a significant life event that concerns the development of lineage in the family and social stability. Around the world, there are many customs related to marriage. From ancient times until today, traditional wedding ceremonies are still considered significant events in a person's life. This happy event marks an important milestone in life; hence, almost all the time, the wedding ceremony is grand and solemn. This study aims to find the similarities between the wedding customs of the Uighur tribe in China and the Javanese people in Indonesia. The author uses a qualitative comparative method, namely comparing references from one source to other sources to get information that matches the author's needs. The result of this research is that the author found out that there are similarities in the traditional wedding processions of the Uyghur and Javanese tribes, including the proposal procession, engagement, sending engagement gifts, wedding ceremonies and going to the groom's house. The length of time for the traditional Uyghur and Javanese weddings is the same, which is two to three days. Then, the differences between traditional Javanese and Uighur weddings lie in wedding attire, religious traditions, music and dance.